FAKTOR YANG MEMENGARUHI PENDAPATAN USAHATANI BAWANG MERAH DI DESA TAMBAN KECAMATAN PAKEL KABUPATEN TULUNGAGUNG (Analysis Of Factors Influencing Shallot Farming Production And Income In Tamban Village, Pakel District, Tulungagung Regency) - SANTOSO, EKO; GUNAWAN, CAKTI INDRA; SETIAJI, JATMIKO (Universitas Mulawarman (University of Mulawarman), 2025)
This study aims to identify and examine various factors that influence the income of shallot farmers in Tamban Village, Pakel District, Tulungagung Regency.The methodology applied is a survey with a quantitative approach.The research location was purposively selected considering that Tamban Village is the main area for red onion production in Tulungagung Regency.As many as 30 red onion farmers were involved as respondents, selected using the simple random sampling technique based on the Slovin formula.The independent variables studied include land area, seed type, fertilizer use, labor, and farming experience, while the dependent variable is the income from shallot farming.Data were analyzed using multiple linear regression, starting with classical assumption tests.The research findings reveal that simultaneously, all independent variables have a positive and significant impact on the income of red onion farmers, with a coefficient of determination value of 85.8%.Partially, the three variables that significantly affect the income of shallot farming are land area, fertilizer, and labor.The land area variable has the greatest impact on increasing income, followed by the fertilizer and labor variables.Meanwhile, the variables of seed type and farming experience do not show a significant influence on the income of shallot farming in the research location.